Spectral coding performance under free space optical medium - Abdul Rahman, Kram; Rashidi, C. B. M.; Aljunid, S. A.; Khairul Fikri, Tamrin; Rudiyanto, P. Jong; Dyg Norkhairunnisa, Abang Zaidel (Institute of Advanced Engineering and Science., 2019)
This paper focus on performance of code Zero Correlation-Correlation (ZCC) in free space optical communication. The ZCC code has a superior characteristic which eliminate the overlapping code between any users. Due to this high class characteristic, the code improves the performance of the conventional code in free space optical environment. In this paper the analysis performance of bit error rate is considering the avalanche (APD) noise, thermal noise and multiuser interference. The result shows that ZCC code improve the performance of conventional code in term of number of users, power received and data bit rate.